Speaking Practice in Deutschclub Universitas Negeri Malang - Twinky Andrean Trianantyas (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2019)
Speaking is one of the hardest language skills and it is relatively difficult to master. Nevertheless, the german students learn the skill through the learning activities, intracuricular, cocuricular and extracuricular. The aim of this research is to describe the speaking practice in Deutschclub and the influence of the participation in Deutschclub on the speaking ability. The research used the descriptive quantitative method and there are two instruments used to collect the data. The first intsrument ist questionnaires about speaking practice of german students in the year 2018 in Deutschclub, the learning activity in Deutschclub and the speaking ability. The second instrument is the documentation from the grades and tasks from the students. The sample is 68 german students in the year 2018, who took the course Konversation I.According to the results of the reasearch, it can be summarized that most of german students do speaking practice and train in the planned time. However, there are some aspects of speaking skills, that were not fulfilled, although they got und learned them in the course. It was found, that Deutschclub can be an answer to the problems and for the german students, who want to improve their speakings skill with each other. They can also discuss without hesitation about german language und culture, so that they can establish contacts with other german students. On the other hand, Deutschclub couldn’t improve students’ speaking skill because of the low attendance and low participation of the students during the Deutschclub.